Pengaruh Gaya Kepemimpinan Transformasional Dan Kompensasi Terhadap Kinerja Karyawan Melalui Komitmen Organisasi Sebagai Variabel Mediasi - Elfa Shita Hardini; Sutrisno; Rita Meiriyanti (Universitas Kristen Indonesia Toraja, 2023)
This study aims to determine the influence of transformational leadership style and compensation through mediating variables of organizational commitment to employee performance CV Multi Warna Grafika Semarang, with saturated sample collection techniques taken based on non-probability sampling techniques. Data analysis was carried out using the Partial Least Square (PLS) method using SmartPLS 3 software. The results showed that transformational leadership style affects employees' organizational commitment. Compensation affects the organizational commitment of employees. Organizational commitment affects employee performance. Transformational leadership style has no effect on employee performance. Compensation has no effect on employee performance. Transformational leadership styles influence employee performance mediated by organizational commitment. Compensation affects employee performance mediated by organizational commitment.